Dielectric investigations in Sr0.75Ba0.25Nb2O6 relaxor ferroelectric thin films - Santos, I. A.; Mendes, R. G.; Eiras, J. A.; Guerra, J. de Los S.; Araujo, E. B. [UNESP] (Springer, 2009)
The dielectric properties of Sr0.75Ba0.25Nb2O6 relaxor ferroelectric thin films were carefully analyzed. In contrast to bulk samples which present three distinct dielectric relaxation phenomena Sr0.75Ba0.25Nb2O6 thin films present only two of them. The suppression of the third anomaly can be mainly attributed to the narrow grain size distribution of nanograins and weak tensile strains imposed to the film from the substrate. The whole set of results point to the interpretation of a dielectric response characteristic of mesoscopic structure, which is composed of clusters and nanodomains.